Republic of Azerbaijan : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
Azerbaijan faced unprecedented challenges in 2020. The combined COVID-19 and oil price shocks pushed the economy into recession. A sizeable relief package helped cushion the economic impact from this shock, and the economy has started to recover. Yet the medium-term outlook remains subdued. The long-term fiscal position is unsustainable as oil resources are expected to run out by mid-century. The authorities have laid out strategic goals of accelerated yet sustainable socio-economic development over the next decade and are developing policy plans to that end.